Hidden attractions of administration : the peculiar appeal of meetings and documents /: the peculiar appeal of meetings and documents. (2021) - Åkerström, Malin; Jacobsson, Katarina; Andersson Cederholm, Erika, 1965-; Wästerfors, David
No abstract available